2023
DOI: 10.1002/asia.202201296
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐Base Chemistry Provides a Simple and Cost‐Effective Route to New Redox‐Active Ionic Liquids

Abstract: Redox‐active ionic liquids (RAILs) hold great promise as high density electrochemical energy storage materials, but are hampered by high costs and low bulk conductivities. In this work, we introduce and electrochemically characterise novel redox‐active protic ionic liquids (RAPILs) formed by acid‐base neutralisation from cheap and plentiful starting materials. We also demonstrate a novel RAIL‐in‐IL solvent system for electrochemical characterisation of RAPILs, which enables efficient and cost‐effective determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Recent work highlighting the need to electronically decouple the redox-active centre from any ionizable functional group in PIL systems promises greater investigation in this vein. 246 Increasing the accessible energy density and widening the operating temperature window of the vanadium system by selection of the appropriate PIL may also deliver tangible improvements to the incumbent technology if long-term cyclability is established. 243 Proton battery technology is nascent but PILs appear to be ideal candidates due to their inherently high proton conductivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent work highlighting the need to electronically decouple the redox-active centre from any ionizable functional group in PIL systems promises greater investigation in this vein. 246 Increasing the accessible energy density and widening the operating temperature window of the vanadium system by selection of the appropriate PIL may also deliver tangible improvements to the incumbent technology if long-term cyclability is established. 243 Proton battery technology is nascent but PILs appear to be ideal candidates due to their inherently high proton conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, three main avenues have been pursued, that of using PILs as solvents to access higher concentrations of active species, 243,244 using PILs as part of the fabrication of novel membranes, 245 or indeed using PILs as redox-active species themselves. 246 In 2020, Zhou et al showed that [HN 122 ][TfO] could be used effectively to produce asymmetric porous membranes for use in vanadium-based RFBs. 245 The PIL was dissolved in a sulfonated poly(ether sulfone) (SPES) solution and via phase inversion and PIL removal, a membrane with a dense SPES layer and a highly porous layer was fabricated.…”
Section: Redox Flow Batteriesmentioning
confidence: 99%
See 2 more Smart Citations